2017
DOI: 10.1109/lawp.2017.2650863
|View full text |Cite
|
Sign up to set email alerts
|

Channel Characteristics of Dynamic Off-Body Communications at 60 GHz Under Line-of-Sight (LOS) and Non-LOS Conditions

Abstract: This letter investigates the first-order characteristics of dynamic off-body communications channels at 60 GHz. In particular, we have studied signal propagation from a chest-worn millimeter-wave transmitter as an adult male walked toward and then away from a hypothetical base station. The mobile line-ofsight (LOS) and non-LOS (NLOS) channel measurements have been conducted in a diverse range of environments, including a hallway, an open office, an anechoic chamber, and an outdoor car park. In this study, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Our claim is that different numerologies will fare better under blockage conditions, and hence may be used to improve the mmWave user performance. We verify our claim by analysing the mmWave link performance using the numerologies available for 5G mmWave systems, under a range of blockage scenarios, defined and empirically-validated in [10]. Our results show that there is a trade-off between the high transmission efficiency, achieved with longer TTIs, and the high probability of LOS transmission, achieved using shorter TTIs.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Our claim is that different numerologies will fare better under blockage conditions, and hence may be used to improve the mmWave user performance. We verify our claim by analysing the mmWave link performance using the numerologies available for 5G mmWave systems, under a range of blockage scenarios, defined and empirically-validated in [10]. Our results show that there is a trade-off between the high transmission efficiency, achieved with longer TTIs, and the high probability of LOS transmission, achieved using shorter TTIs.…”
Section: Introductionmentioning
confidence: 60%
“…The AP is installed at a height h A above the UE level, as illustrated in Figure 2a. This setup shall generalise over the two deployment scenarios considered in [10], but is also in-line with the 3GPP-defined scenarios for 5G mmWave system evaluation [27]: indoor office with ceiling-mounted access points and outdoor car-park with lamppost mounted access points. We assume the resource allocation decision in the AP is made every τ ms, which we refer to as the scheduling interval (SI).…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been performed to investigate the statistical characteristics of the small-scale fading experienced in indoor mm-wave communications channels at 60 GHz [3][4][5]. For example, the small-scale fading observed in off-body communications channels was characterized in [3] using the Rice and Nakagami-m distributions, while in [4] a similar methodology was used to study UE-to-eNB channels. In [5], it was found that the Rice fading model provided the best fit to the measurement data collected in LOS conditions within an indoor laboratory environment.…”
Section: Introductionmentioning
confidence: 99%